PENDIDIKAN KELUARGA BERBASIS FITRAH PADA Q.S LUQMAN AYAT 12-19 - Dzilla Mardiah Nurzakiah, - (2020)
This research is underlain by the writer's concern towards the conditions of most youth at present. The character deterioration and the moral degeneration are rampant, proven by the significant increase of cases of juvenile delinquency and behavioral deviation year by year. Considering the aforementioned cases, after being learned, it is found that the root of the problem comes from home. Education from the family at home is not optimally taught, or it is even improperly implemented. Parents are neglectful and do not prepare themselves with education skills even though the conditions of the era are constantly changing. Parents do not understand their roles and have no idea about the potential of fitrah as one of the important things in carrying the trust to educate their children, whereas all of the things which have been created by Allah have creation purposes. In addition, in Al-Qur'an, there are many figures created by Allah to be used as the role models for us. One of them is the story of Luqman al-Hakim in the 12th-19th verses of surah Luqman. With regard to the research purpose, this research aims to find out mufassirs' view about the 12th-19th verses of surah Luqman which later relearned to find values of fitrah-based family education in the aforementioned verses, so that eventually, the findings can be implemented in the family education. Regarding the interpretation method, this research uses tahlīli and mauḍui interpretation methods. The data collection technique used in this research is the literature review. The data gained include Al-Qur'an as the main source completed by the interpretations, books, and journal articles which are related to the research problems as the secondary source. The research results show that the values of fitrah-based family education are found in the 12th-19th verses of surah Luqman; those are (1) fitrah of having faith, which includes (a) fitrah of being religious/believing God and (b) fitrah of having morals and (2) fitrah of learning and reasoning.